Implementation of Active Learning-Based Arabic Learning at Muhammadiyah 5 Palembang Senior High School - Alfiyanto, Afif; Hidayati, Fitri; Riyadi, Ivan; Batin, Mail Hilian (Al-Hijr: Journal of Adulearn World, 2022)
This study aims to determine and understand how the implementation of active learning and student activity in Arabic learning activities. This research is qualitative, using a qualitative approach to phenomenological studies and descriptive methods by taking the background at Muhammadiyah 5 Palembang Senior High School. The data sources of this study were Arabic language teachers and class X students of Muhammadiyah 5 Palembang Senior High School. Data collection methods used are observation, interviews, and documentation. Data analysis techniques used are data reduction, data presentation, and data verification. The results showed that 1) the implementation of active learning by applying three stages, namely a) preliminary (pre-instructional), namely the teacher opened the lesson by asking about students' attendance, repeating the previous learning materials; b) the implementation stage (instructional), namely the stage of conveying the learning content. explain the learning objectives that must be achieved by students, the teacher provides concrete examples, and uses learning media to clarify the discussion of each subject matter; and d) The closing stage (evaluation), where the teacher asks students questions about the material discussed, gives homework assignments, and informs the main material to be discussed at the next meeting. 2) student activity in learning Arabic is an effort or activity carried out by students when the teacher explains Arabic learning material. Students show the courage to ask about unknown learning materials, participate in discussing learning with friends, students creative, have interest and are independent in thinking, have responsibility and confidence in doing assignments that have not been studied, and students can learn independently.